Pengaruh Kualitas Website terhadap Minat Beli Konsumen - Fadhlan Thariq; Yen Efawati (Asosiasi Ahli Administrasi Indonesia, 2024)
This study examines the impact of website quality on consumer purchase interest, focusing on ease of use, interaction, and information quality as key assessment components. A quantitative research approach was employed, utilizing data from 107 respondents residing in Greater Bandung who had interacted with the Rumahweb website. Data was collected via questionnaires distributed through Google Forms to obtain primary data. The analysis revealed that website quality positively influences consumer purchase interest, accounting for 64.4% of the variance in purchase intent. Simple regression analysis was conducted to test the hypothesis, confirming the significance of website quality in driving consumer engagement and purchase decisions. This research underscores the importance of maintaining high-quality websites to enhance consumer interest in products and services.